Pedoman Pemberian Tablet Tambah Darah (TTD) Bagi Remaja Putri di SMA Negeri 8 Makassar - Endang Sulistyowati; Sukmawati Sukmawati; Ary Handayani; Nadia Nadia; Hutri Rara’ Panggalo; Jimmy Sampe (PPNI UNIMMAN, 2023)
The provision of blood supplement tablets in adolescent girls currently has an urgency to prevent anemia and increase iron reserves in the body which is a provision in preparing healthy quality and productive adolescent girls. Adolescent girls have a menstrual phase every month, plus their rapid growth, so they need a strong and balanced nutritional intake. One of them is by fulfilling the needs of iron (Fe) in the body. Adolescent girls who experience anemia can reduce intelligence, productivity, and learning achievement. This service aims to provide socialization to students to find out the guidelines for taking blood supplement tablets and provide insight to students about the impact of anemia and its prevention. The method used in this service activity is counseling with lecture methods and active discussion between presenters and participants. Students were briefed to follow the guidelines for giving blood supplement tablets according to the guidelines given by the Ministry of Health, namely 1 tablet every week for 1 year (52 weeks). Blood supplement tablets are nutritional supplements containing 60 mg of elemental iron and 0.25 mg of folic acid (in accordance with WHO recommendations). The conclusion of this service activity is that many students have not consumed blood supplement tablets regularly so that after counseling it is expected that students regularly consume TTD.